DEVELOPMENT OF MARKETING AND PROMOTIONAL STRATEGIES SAMARINDA CITY MSME USES AN INTEGRATED MARKETING COMMUNICATION APPROACH - Tisya Ayu Andriani, Imam Nazarudin L, Risdayanti Dedy Effendi, Yonathan Luhat, (LPPM of NAROTAMA UNIVERSITY, 2025)
The Indonesian economy is required to be more creative, the creativity of entrepreneurs, especially medium and small businesses is really required to maintain their businesses. The addition of creativity of these entrepreneurs is called the creative economy which is a development of the economic sector. The purpose of this study is to develop marketing and promotional strategies to boost the creative economy of Samarinda City that are proactive and sustainable. Samarinda City MSME entrepreneurs are expected to be able to improve quality and quality, as well as open up employment opportunities. MSMEs are expected to be able to survive and be competitive in the era of globalization and digitalization. MSME entrepreneurs are expected to have high creativity and innovation. This study uses a descriptive qualitative approach, data analysis using time triangulation. Data collection techniques through in-depth interviews and observations on social media. The results of this study explain that Samarinda City MSMEs are able to maintain their businesses and can increase sales because they implement the marketing and promotional strategies developed, namely integrated marketing communications which are currently very popular among entrepreneurs. MSMEs can increase their sales by using direct marketing, online marketing, sales promotion and advertising for marketing. As a result, MSMEs can survive and increase sales by two-fold and can add employees and are able to develop businesses outside the region. In the future, MSMEs in Samarinda City must optimize the use of features on social media such as creating content more often and uploading it on social media to increase engagement (online marketing) and advertising which can ultimately increase sales and brand awareness and make innovations for the latest and contemporary products.